Lachmann-Mosse House | Chamonix, France Architecture | Residences... - Auteur inconnu... (Leo Baeck Institute, Center for..., 1930)
Notice issue d Europeana. unknown
Droits : http://rightsstatements.org/vocab/InC-EDU/1.0/
Keywords: europeana; image; patrimoine europeen; Bibliothèque numerique; iconographie; Iconographie